Determination Of Ground Structure Using Microtremor Array Method - Cheah, Yi Ben (Universiti Sains Malaysia, 2018)
Ground structure characteristic is an important parameter in seismic site effect evaluation for earthquake structural design. Many geophysical methods can be used to estimate ground structure. The best field measurement option that requires least field effort and yet producing accurate estimation is the main concern of this study. This study applies microtremor array observation method to investigate the accuracy of VS profile estimated using Spatial Autocorrelation (SPAC) and Centerless Circular Array (CCA) methods of various array radii. Based on VS profile obtained, the effect of considering sediment thickness of more than 30m on ground classification is investigated. Microtremor array observation was conducted at a total of nine sites in Kuala Lumpur and Penang with large (10m radius and above), medium (5m radius) and small (1m radius) array. When using SPAC method, larger array gives better VS profile estimation. When using CCA method, medium array gives better estimation among three array sizes. CCA method gives better estimation as compared to SPAC method when medium array is used in observation. Thus, CCA method is more favourable in term of fieldwork efficiency. Out of five sites with sediment thickness more than 30m, four sites exhibit ground type changes by reducing one to two classes and the other one remains unchanged. Although the ground type remains unchanged, but the acceleration response increases. These changes in ground type have affected low to medium rise buildings within the fundamental periods of 0.1s to 1.0s significantly because the acceleration response increases drastically when sediment thickness more than 30m is considered.